BMI as a predictor of high fasting blood glucose among people living with HIV in the Asia‐Pacific region. Issue 2 (24th June 2022) - Khuon, Dyna; Rupasinghe, Dhanushi; Saphonn, Vonthanak; Kwong, Tsz‐Shan; Widhani, Alvina; Chaiwarith, Romanee; Ly, Penh Sun; Do, Cuong Duy; Avihingsanon, Anchalee; Khusuwan, Suwimon; Merati, Tuti Parwati; Van Nguyen, Kinh; et al.
Abstract: Background: Non‐Asian body mass index (BMI) classifications are commonly used as a risk factor for high fasting blood glucose (FBG). We investigated the incidence and factors associated with high FBG among people living with HIV in the Asia‐Pacific region, using a World Health Organization BMI classification specific to Asian populations. Methods: This study included people living with HIV enrolled in a longitudinal cohort study from 2003 to 2019, receiving antiretroviral therapy (ART), and without prior tuberculosis. BMI at ART initiation was categorized using Asian BMI classifications: underweight (<18.5 kg/m 2 ), normal (18.5–22.9 kg/m 2 ), overweight (23–24.9 kg/m 2 ), and obese (≥25 kg/m 2 ). High FBG was defined as a single post‐ART FBG measurement ≥126 mg/dL. Factors associated with high FBG were analyzed using Cox regression models stratified by site. Results: A total of 3939 people living with HIV (63% male) were included. In total, 50% had a BMI in the normal weight range, 23% were underweight, 13% were overweight, and 14% were obese. Median age at ART initiation was 34 years (interquartile range 29–41). Overall, 8% had a high FBG, with an incidence rate of 1.14 per 100 person‐years. Factors associated with an increased hazard of high FBG included being obese (≥25 kg/m 2 ) compared with normal weight (hazard ratio [HR] = 1.79; 95% confidence interval [CI] 1.31–2.44; p  < 0.001) and older age compared with those aged ≤30 years (31–40 years: HR = 1.47; 95% CI 1.08–2.01; 41–50 years: HR = 2.03; 95% CI 1.42–2.90; ≥51 years: HR = 3.19; 95% CI 2.17–4.69; p  < 0.001). Conclusion: People living with HIV with BMI >25 kg/m 2 were at increased risk of high FBG. This indicates that regular assessments should be performed in those with high BMI, irrespective of the classification used.